The art of deception : controlling the human element of security - Mitnick, Kevin, 1963-2023; Simon, William L., 1930- (Wiley, 2002)
Focusing on the human factors involved with information security, Mitnick explains why all the firewalls and encryption protocols in the world will never be enough to stop a savvy grifter intent on rifling a corporate database or an irate employee determined to crash a system. With the help of many fascinating true stories of successful attacks on business and government, he illustrates just how susceptible even the most locked-down information systems are to a slick con artist impersonating an IRS agent. Narrating from the points of view of both the attacker and the victims, he explains why each attack was so successful and how it could have been prevented. Mitnick also offers advice for preventing these types of social engineering hacks through security protocols, training programs, and manuals that address the human element of security.